(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The article introduces possibility how to use special material from plasterboard back to the production of plasterboards. The recycled material was prepared from standard plasterboards KNAUF WHITE (it means plasterboard type A according to European standard EN 520) [1]. Plasterboards were crushing, micromilled and separated from the paper on recycling line, which was developed in company Lavaris s.r.o. [2]. This material was used as an inert to the standard recipe instead of stucco. There were checked the influence on properties of final plasterboards in comparison with standard plasterboards.